AKSIOLOGI BUDAYA BUGIS MAKASSAR TERHADAP PRODUK PERATURAN DAERAH (PERDA) DI SULAWESI SELATAN (Studi Politik Hukum) - Said, Zainal (DIKTUM: Jurnal Syariah dan Hukum, 2011)
In general most of the tribes in South Sulawesi has a relationship, both in terms of language, as well as culturally. Bugis Makassar in public life, customs is a factor that was crucial. Indigenous is a manifestation of the "philosophy of life" man Bugis Makassar in their social institutions and occupy the highest positions in the social norms that govern the behavior patterns of peoples lives. Social system or societal values that were born under customary provisions have established patterns of behavior and views of human life Bugis Makassar. Adat is the key idea underlying all of his relationships, both with fellow human beings, social institutions, as well as with the natural surroundings, even with the macrocosm. As customs, rules accustomed, certainly can be called traditional, but not in the sense panngaderreng essential. Such a custom would be opposed by panngaderreng because panngaderreng actually build dignity and human dignity. Panngaderreng happenings include ade about talking, about rapang, about wari and about sara. But the progressive side of the law, look to a tendency to ignore the custom that we have and nurture over the years. And penetration protection against the formation of customary law are sometimes forgotten even element values in it have not been able to exist in the underlying fundamental laws of various products. Since most products are still legal hegemony in the interests of society who tend to put in a position pheriperial, or known by the politically conditioned, especially in the context of law in South Sulawesi regressus